Groundwater Assessment for Drinking and Irrigation proposes of Ar Rajmah Area, NE Libya - Fares F. Fares , (Scientific Journal of University of Benghazi, 2020)
The aim of the present work is to assess the groundwater quality for drinking and irrigation uses in Ar Rajmah area, NE Libya. The result revealed that the groundwater is hard to fresh water and characterized by Ca-Mg-Cl type, due to weathering of carbonate rocks that controlling water chemistry. The groundwater is supersaturated with halite, gypsum, dolomite and calcite. In general the groundwater in the studied samples is suitable for drinking and irrigation proposes, regardless of slight increase in (NO3) value which should be treated.